The Influence of Cleanliness, Water Flow, Complaint Response, and Network Maintenance on Customer Satisfaction Levels at PDAM Tirta Makmur, Sukoharjo Regency - Firmansyah, Muhammad Jibran; Kusdiyanto, Kusdiyanto (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The purpose of this study was to examine how water cleanliness, flow continuity, complaint response, and network maintenance affect customer satisfaction at PDAM Tirta Makmur in Sukoharjo Regency. This study employed an explanatory quantitative approach and conducted a survey involving 380 participants. Data were collected through questionnaires and tested using multiple linear regression analysis. The results indicated that all independent variables influenced customer satisfaction both collectively and individually. The variable that most significantly affected customer satisfaction was complaint response, followed by network maintenance, water cleanliness, and flow continuity. According to the regression model used, which had an R Square value of 0.747, these four variables accounted for 74.7% of the variation in customer satisfaction. This study was limited to PDAM customers in Sukoharjo. It offers originality by emphasizing the importance of responsiveness and infrastructure maintenance in improving public services in the clean water sector.